Isolation, identification and assessment of antibiotic resistance of common bacteria in pork meat in kota bharu, kelantan - Kirthekka A/P Balachandran (2022)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement on the course DVT 55204 – Research Project. Foodborne illness has been a growing curve over the past years and limited studies have been carried out to prove this in Malaysia especially in the State of Kelantan. Additionally, this is a study to detect any bacteria isolated from pork meat in Kota Bharu, Kelantan, as well as the antibiotic resistance pattern. A total of 30 pork meat samples were collected from 30 different pork vendors in wet markets in Kota Bharu, Kelantan. Based on the results from morphological colony growth on bacterial culture and biochemical tests, the isolated bacteria were Bacillus cereus, Enterococcus spp., Enterobacter spp., Escherichia coli, Klebsiella sp., Proteus sp., Pseudomonas sp., Salmonella sp., and Streptococcus spp. From the results, it was found that the isolated bacteria were resistant to various antibiotics including ampicillin, sulphonamides, trimethoprim (18%), tetracycline (14%), doxycycline (8%) and gentamicin (6%), respectively. These findings showed that the bacterial contamination in pork meat can cause foodborne illness and resistant to common antibiotics used in human and animal medicine which may potentially spread to public. Keywords: Antibiotic resistance, Awareness, Bacteria, Pork